1238. A National Comparison of Antibiograms Between Veterans Affairs Long-Term Care Facilities and Affiliated Hospitals. (26th November 2018) - Tolg, Maria-Stephanie; Caffrey, Aisling; Appaneal, Haley; Jump, Robin; Lopes, Vrishali; Dosa, David; LaPlante, Kerry
Abstract: Background: Long-term care facilities (LTCFs) face several barriers to creating antibiograms. Here, we evaluate if LTCFs can use antibiograms from affiliated hospitals as their own antibiogram. Methods: Facility-specific antibiograms were created for all Veterans Affairs (VA) LTCFs and VA Medical Centers (VAMCs) for 2017. LTCFs and affiliated VAMCs were paired and classified as being on the same campus or geographically distinct campuses based on self-report. For each pair, Escherichia coli susceptibility rates (%S) to cefazolin, ceftriaxone, cefepime, ciprofloxacin, nitrofurantoin, sulfamethoxazole/trimethoprim, ampicillin/sulbactam, piperacillin/tazobactam, and imipenem were compared. As guidelines discourage empiric use of antibiotics if susceptibility rates are <80%, we assessed clinical discordance between each LTCF and affiliated VAMC antibiogram at a threshold of 80% susceptible. The proportions of concordant susceptibilities between LTCFs and VAMCs on the same campus vs. geographically distinct campuses were compared using Chi-square tests. Results: A total of 119 LTCFs and their affiliated VAMCs were included in this analysis, with 70.6% ( n = 84) of facilities located on the same campus and 29.4% ( n = 35) on geographically distinct campuses. The table below shows the overall clinical concordance (agreement) of LTCFs with their affiliated VAMC in regards to E. coli %S to the compared antibiotics. No significant differences were found when comparing LTCFs on the same campus vs. geographically distinct campuses. Conclusion: Antibiograms between LTCFs and affiliated VAMCs had a high concordance, except for sulfamethoxazole/trimethoprim, cefazolin and ceftriaxone in regards to susceptibility rates of E. coli . Facilities on the same campus were found to have similar concordance rates to geographically distinct facilities. Future studies are needed to investigate how the various approaches to creating LTCF-specific antibiograms are associated with clinical outcomes. Disclosures: M. S. Tolg, Veterans Affairs: Investigator, Research grant. A. Caffrey, Veterans Affairs: Investigator, Research grant. H. Appaneal, Veterans Affairs: Grant Investigator, Research grant. R. Jump, Veterans Affairs: Investigator, Research grant. V. Lopes, Veterans Affairs: Investigator, Research grant. D. Dosa, Veterans Affairs: Grant Investigator, Research grant. K. LaPlante, Veterans Affairs: Investigator, Research grant.